2012
DOI: 10.1074/jbc.m111.297580
|View full text |Cite
|
Sign up to set email alerts
|

Human Heat Shock Protein 105/110 kDa (Hsp105/110) Regulates Biogenesis and Quality Control of Misfolded Cystic Fibrosis Transmembrane Conductance Regulator at Multiple Levels

Abstract: Background: Hsp105 prevents protein aggregation, accelerates Hsc70 nucleotide exchange, and functionally relates to Hsp90. Results: Hsp105 facilitates CFTR quality control coincident with translation, enhances its post-translational folding, and stabilizes misfolded CFTR at cell periphery. Conclusion: Hsp105 is a versatile regulator in CFTR folding and quality control. Significance: Hsp105 plays distinct roles in CFTR folding from other Hsc70 nucleotide exchange factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
39
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 79 publications
0
39
0
Order By: Relevance
“…Sse1 has been previously shown to have a role in protein refolding in vitro and in vivo and in de novo folding in vivo (11,12). Human Hsp105 (Hsp110) has been shown to be important in CFTR folding in vivo (54). Roles of the other NEFs have not been fully investigated.…”
Section: Resultsmentioning
confidence: 99%
“…Sse1 has been previously shown to have a role in protein refolding in vitro and in vivo and in de novo folding in vivo (11,12). Human Hsp105 (Hsp110) has been shown to be important in CFTR folding in vivo (54). Roles of the other NEFs have not been fully investigated.…”
Section: Resultsmentioning
confidence: 99%
“…For example, none of the combinations that included Hsp105 were able to fold luciferase in our assays, suggesting that it may assist Hsp70 with other functions, such as cystic fibrosis conductance receptor trafficking and quality control (75). On the basis of this idea, it is intriguing to speculate that an impressive number of permutations might be generated by combinatorial assembly of human cochaperones.…”
Section: Discussionmentioning
confidence: 99%
“…However, members of the Hsp110 family lack the ability to refold clients (72,73), and, rather, they have a prominent NEF function on Hsp70s (41,74). Recently, human Hsp110 (termed Hsp105) has been shown to help coordinate stabilization of the cystic fibrosis conductance receptor (75), suggesting that this NEF function might be functionally important. However, there is little known about the biochemistry of Hsp105 and its relative position in the hierarchy of eukaryotic NEFs.…”
Section: Hsp105 Competes With Bag Proteins and Acts As A Nef-mentioning
confidence: 99%
“…The heat shock 70-kDa protein family and related cochaperones regulate biogenesis and quality control of CFTR (8)(9)(10), and both wildtype and common mutated forms of CFTR are degraded by ubiquitin-mediated proteasomal degradation (8,9). CFTR peripheral quality control occurs after the Golgi compartment, where CFTR localized to the cell surface undergoes endocytosis and recycling by a ubiquitin-dependent endosomal sorting system.…”
Section: Discussionmentioning
confidence: 99%
“…We showed that imposing monoubiquitination on wild-type (wt) and F508del CFTR leads to increased preservation of band B core glycosylated CFTR (7). Ubiquitination of CFTR is important for its regulation and quality control process (8)(9)(10), including ubiquitin-mediated proteasomal degradation (8,9) and recycling (11,12). However, the ubiquitination sites on wt CFTR, mechanism of degradation, and regulation of recycling are largely unknown.…”
mentioning
confidence: 99%